Opisthorchis viverrini and Haplorchis taichui: Development of a multiplex PCR assay for their detection and differentiation using specific primers derived from HAT-RAPD - Wongsawad C. (2014)
Specific primers for the detection of Opisthorchis viverrini and Haplorchis taichui were investigated by using the HAT-RAPD PCR method. Fourteen arbitrary primers (Operon Technologies) were performed for the generation of polymorphic DNA profiles. The results showed that a 319bp fragment generated from the OPA-04 primer was expected to be O. viverrini-specific while a 256bp fragment generated from the OPP-11 primer was considered to be H. taichui-specific. Based on each sequence data, two pairs of specific primers were designed and sequences of each primer were as follows; H. taichui; Hapt_F5'-GGCCAACGCAATCGTCATCC-3'and Hapt_R1 5'-CTCTCGACCTCCTCTAGAAT-3' which yielded a 170bp PCR product. For O. viverrini, OpV-1F: 5'-AATCGGGCTGCATATTGACCGAT-3' and OpV-1R: 5'-CGGTGTTGCTTATTTTGCAGACAA-3' which generated a 319bp PCR product. These specific primers were tested for efficacy and specific detection for all parasites DNA samples. The results showed that 170 and 319bp specific PCR products were generated as equivalent to positive result in H. taichui and O. viverrini, respectively by having no cross-reaction with any parasites tested. PCR conditions are recommended at 68°C annealing temperature and with 0.5mM magnesium chloride (Mg Cl 2). Additionally, specific primers developed in this study were effective to determine the presence of both parasites in fish and snail intermediate hosts, which the DNA of O. viverrini was artificially spiked since it is rarely found in northern Thailand.The H. taichui and O. viverrini-specific primers successfully developed in this study can be use for epidemiological monitoring, preventing management and control programs. © 2012 Elsevier Inc.